Electrochemical Genotoxicity Assay Based on a SOS/umu Test Using Hydrodynamic Voltammetry in a Droplet - Kazuharu Sugawara; Masami Fukushima; Shigeru Taguchi; Noriko Hata; Kazuto Sazawa; Yasuaki Nanayama; Hideki Kuramitz (Sensors, 2012)
The SOS/umu genotoxicity assay evaluates the primary DNA damage caused by chemicals from the β-galactosidase activity of S. typhimurium. One of the weaknesses of the common umu test system based on spectrophotometric detection is that it is unable to measure samples containing a high concentration of colored dissolved organic matters, sediment, and suspended solids. However, umu tests with electrochemical detection techniques prove to be a better strategy because it causes less interference, enables the analysis of turbid samples and allows detection even in small volumes without loss of sensitivity. Based on this understanding, we aim to develop a new umu test system with hydrodynamic chronoamperometry using a rotating disk electrode (RDE) in a microliter droplet. PAPG when used as a substrate is not electroactive at the potential at which PAP is oxidized to p-quinone imine (PQI), so the current response of chronoamperometry resulting from the oxidation of PAP to PQI is directly proportional to the enzymatic activity of S. typhimurium. This was achieved by performing genotoxicity tests for 2-(2-furyl)-3-(5-nitro-2-furyl)-acrylamide (AF-2) and 2-aminoanthracene (2-AA) as model genotoxic compounds. The results obtained in this study indicated that the signal detection in the genotoxicity assay based on hydrodynamic voltammetry was less influenced by the presence of colored components and sediment particles in the samples when compared to the usual colorimetric signal detection. The influence caused by the presence of humic acids (HAs) and artificial sediment on the genotoxic property of selected model compounds such as 4-nitroquinoline-N-oxide (4-NQO), 3-chloro-4-(dichloromethyl)-5-hydroxy-2(5H)-furanone (MX), 1,8-dinitropyrene (1,8-DNP) and 1-nitropyrene (1-NP) were also investigated. The results showed that the genotoxicity of 1-NP and MX changed in the presence of 10 mg∙L–1 HAs. The genotoxicity of tested chemicals with a high hydrophobicity such as 1,8-DNP and 1-NP were decreased substantially with the presence of 1 g∙L–1 sediment. This was not observed in the case of genotoxins with a low log Kow value.